Testing of Railway Equipment for the Impact on the Track and Turnouts - Abdullayev, Seidulla; Bakyt, Gabit; Abdullayeva, Assel; Duisembayeva, Bakytzhamal; Askenov, Yerlan; Ashirbayev, Galymzhan; Besekenov, Rustam (Communications - Scientific Letters of the University of Zilina, 2024)
The indicators of dynamic qualities that ensure the traffic safety, as well as the permissible impact on the railway track, with the obligatory fulfillment of which the railway rolling stock can be used in the transportation process, are presented in this article. The purpose of this work was to carry out the complex dynamic (running), and the impact on the railway track, tests of the rolling stock, during which simultaneous registration of dynamic processes on the railway rolling stock, and in the elements of the superstructure of the track, is carried out, as well as in elements of turnouts. Dynamic tests were carried out on the track switches from the minimum speed to the maximum possible speed of 50 km/h by the TE33A diesel locomotive during the freight traffic. Meeting the requirement of reproducibility of test conditions and having a typical design of the track structure on wooden or reinforced concrete sleepers.
Keywords: railway track; railway rolling stock; dynamic indicators; turnouts; dynamic testing